Colonic diverticulitis following open-heart surgery: a case report of an unusual postoperative gastrointestinal complication. Issue 6 (22nd June 2020) - Acheampong, Derrick; Boateng, Percy
Abstract: Diverticulitis, though a common gastrointestinal disease, is rare following open-heart surgery. There is insufficient data regarding its incidence and management post-cardiac surgery. Especially in patients with atypical presentation, diagnosis and management can be challenging. This case outlines one such atypical diverticulitis case in which a 57-year-old female patient developed perforated diverticulitis with pelvic abscess accumulation following left ventricular aneurysm (LVA) repair. Diagnosis, appropriate management and treatment approaches are discussed. Cardiac surgeons should consider the possibility of diverticulitis in patients reporting nonspecific abdominal pain following cardiac surgery to ensure early diagnosis and institution of appropriate treatment to prevent associated adverse outcomes.